If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3/7)x=66
We move all terms to the left:
(3/7)x-(66)=0
Domain of the equation: 7)x!=0We add all the numbers together, and all the variables
x!=0/1
x!=0
x∈R
(+3/7)x-66=0
We multiply parentheses
3x^2-66=0
a = 3; b = 0; c = -66;
Δ = b2-4ac
Δ = 02-4·3·(-66)
Δ = 792
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{792}=\sqrt{36*22}=\sqrt{36}*\sqrt{22}=6\sqrt{22}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-6\sqrt{22}}{2*3}=\frac{0-6\sqrt{22}}{6} =-\frac{6\sqrt{22}}{6} =-\sqrt{22} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+6\sqrt{22}}{2*3}=\frac{0+6\sqrt{22}}{6} =\frac{6\sqrt{22}}{6} =\sqrt{22} $
| 3−6f=-6f+3 | | 2(x+1)=54 | | -6j−4=-5j+4 | | -10y+10=-7+7y | | 2(5x-11)=18 | | 11x-28+4=108 | | -4+z=6+2z | | 258=-x | | -9(3x-2)=-36 | | -4+6m=6m | | -12h=-6−18h | | z+9=-z−9 | | d+1=3+d | | 42-(2c+)=4(c+6)+c | | 8x+-18x=-10 | | -y=-y+1 | | 1(-x)-(-4)=(-x)-x+1 | | −5x2+100x−520=0 | | -8d−1=-8d−4 | | 22=4s-6s | | 8−8r=-8r+5 | | -5f=-5−5f | | 7-5=1/3(x+12) | | 9m=9m−4 | | -4(1-9h)=-31 | | -3z−8=-2z | | 8f=7f+f | | (x)=4x^2+x+5 | | 3c+6-7=-16 | | 10q=1+9q | | -9c+4=-10c | | -9s+5s=-4s |